2011
DOI: 10.1143/jjap.50.025802
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric Properties of Pb0.98Bi0.02Zr0.51Ti0.48Zn0.01O3 Ceramics

Abstract: On the basis of eutectic behavior of PbTiO3–PbZrO3–Bi(Zn0.5Ti0.5)O3 ternary system, perovskite-structured Pb0.98Bi0.02Zr0.51Ti0.48Zn0.01O3 ceramics were able to be prepared using conventional electronic ceramic processing at low sintering temperature compatible with Ag as inner electrode materials, promising for co-firing technology to fabricate monolithic multilayer piezoelectric transducers. The dependence of its piezoelectric properties on sintering temperature and various dopants were investigated experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Our previous reports experimentally demonstrated that adding Bi(Zn 0:5 Ti 0:5 )O 3 into the Pb(Zr,Ti)O 3 system could reduce the sintering temperature downward 900 C to obtain ceramics with relative density of 94%. 17,18) It is well known that the final density of ceramics is determined by the density ( 0 ) of green pellets and shrinkage rate (Ál=l) after sintering process through ¼ 0 ð1 À ðÁl=lÞ 3 Þ. Under the processing conditions used here, the relative density more than 94% is obtained when the shrinkage rate Ál=l larger than 12%.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Our previous reports experimentally demonstrated that adding Bi(Zn 0:5 Ti 0:5 )O 3 into the Pb(Zr,Ti)O 3 system could reduce the sintering temperature downward 900 C to obtain ceramics with relative density of 94%. 17,18) It is well known that the final density of ceramics is determined by the density ( 0 ) of green pellets and shrinkage rate (Ál=l) after sintering process through ¼ 0 ð1 À ðÁl=lÞ 3 Þ. Under the processing conditions used here, the relative density more than 94% is obtained when the shrinkage rate Ál=l larger than 12%.…”
Section: Resultsmentioning
confidence: 95%
“…In comparison, those for the PMN0PT48 from our previous report, 18) PZT-4, PZT-5A, and PZT-5H from IEEE standards were also presented. From Table I, it was seen that good piezoelectric properties being similar to those commercial ceramics obtained with high sintering temperature above 1200 C are able to be obtained in a lower sintering temperature window for these PMN-PZT-BZT ceramics, and varying PMN content could modify piezoelectric properties to a great extent.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations